Manajemen Pembangunan Kota Pintar: Sinergi Teknologi, Kebijakan Publik, dan Kearifan Lokal - Pradana, Muhammad Rafieq Adi; Putra, Nanda Pramana (LPPM STIE KRAKATAU, 2024)
The development of smart cities is a crucial strategy for improving urban governance efficiency through the utilization of information and communication technology (ICT). However, its implementation in Indonesia still faces various challenges, particularly related to digital infrastructure readiness, unintegrated regulations, and social disparities due to digital transformation. This study aims to analyze the management of smart city development by highlighting the synergy between technology, public policy, and local wisdom as key factors for its success. This research employs a qualitative method with a secondary data analysis approach. The findings indicate that some cities, such as Yogyakarta and Semarang, have successfully adopted smart city concepts based on local wisdom, while other cities, such as Palangkaraya and Tanjung Pinang, still struggle with policy integration and infrastructure challenges. The study emphasizes that an effective smart city development strategy should include clear regulations, enhanced digital literacy among citizens, and collaboration between the government, private sector, academia, and local communities. The integration of technology with social and cultural values is key to achieving an inclusive and sustainable smart city implementation